Implementasi Manajemen Pendidikan Berbasis Sistem Informasi Era Industri 4.0 untuk Branding Lembaga Pendidikan Sekolah Swasta - Abdul Tahir; Muhamad Sigid Safarudin; Ikhsan Amar Jusman; Najaz Shidiq (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2023)
Management of the relationship between educational institutions and the community is essential in the development of the educational institution itself; school branding is also essential in developing educational institutions to create a good image in the eyes of the community. Therefore, the authors researched this matter at Madrasah Ibtidaiyah (MI). ) Muhammadiyah 1 Simo, Ponorogo to analyze how the madrasah public relations (PR) strategy is used and how the school branding is. This study uses a qualitative approach with interviews and observation methods to gather information. The results of this research were: 1) Simo 1 Madrasah Ibtidaiyah Muhammadiyah (MIM), Ponorogo used a strategy by creating harmonious relations between madrasahs and the community so that later both parties cared for each other and could work together in improving the quality of education. The form of concern given by the community to them includes the provision of student classrooms in residents' homes, considering that classrooms at schools are still limited, community service activities in school construction routinely every month, donations of infaq money for school facilities, and the community's willingness to assist school activities. 2) The net result is that in school branding in this industrial era, the institution has a strategy of providing good services and facilities that will create a good image of the madrasa and make people interested in the madrasa based on the school's website to inform the wider community, the programs provided among others: a) tahfidz program, b) madrasah adiwiyata, c) reading the Qur'an ummi method, d) student shuttle car, e) extracurriculars: drum-band, futsal, and badminton. In improving the school's image, its implementation requires the cooperation of all school members, parents of students and the surrounding community through the print media, namely the distribution of banners, brochures and calendars. Technology media is also used for school branding activities, such as publications on the school's official social media, WhatsApp, Facebook, tick-tock, Instagram and the school's website.